Association between number of medications and indicators of potentially inappropriate polypharmacy: a population-based cohort of older adults in Quebec, Canada - Alexandre Campeau Calfat; Justin P. Turner; Marc Simard; Véronique Boiteau; Caroline Sirois (Therapeutic Advances in Drug Safety)
Background: As the number of medications increases, the appropriateness of polypharmacy may become questionable due to the heightened risk of medication-related harm. Objectives: (1) To investigate the relationship between the number of current medications used by older adults and three indicators of potentially inappropriate polypharmacy: (a) the mean number of potentially inappropriate medications (PIMs), (b) the average count of drug–drug interactions, and (c) the anticholinergic burden; (2) To characterize the population-based burden of potentially inappropriate polypharmacy by calculating the proportion of individuals with these indicators. Design: We conducted a population-based observational study using the Quebec Integrated Chronic Disease Surveillance System. Methods: We included all individuals over 65 years insured by the public drug plan on April 1st, 2022. For each individual, we calculated the number of current medications and the number of (a) PIMs (Beers 2019), (b) drug–drug interactions (Beers 2019), and (c) anticholinergic burden (Anticholinergic Cognitive Burden (ACB) scale). The association between the number of medications and these indicators was quantified using linear regression. Prevalence with 99% confidence intervals (CIs) was calculated. Results: A total of 1,437,558 individuals (mean age: 75; 55% female) were included, taking an average of 4.9 medications (±4.1). For each additional medication, the mean number of PIMs, drug–drug interactions, and anticholinergic burden increased by 0.11, 0.04, and 0.17, respectively ( p -trend <0.0001). Nearly half the population (45.5%; 99% CI: 45.5–45.5) had a regimen containing ⩾1 PIMs, ⩾1 drug–drug interaction, or an ACB ⩾3. Conclusion: The strong association between the increasing number of medications and reduced polypharmacy quality underscores the importance of medication count beyond therapeutic indications. With widespread medication use, many older adults face quality issues.